Peran Istri dalam Membantu Perekonomian Keluarga Ditinjau dari Ekonomi Islam (Studi Pasar Tradisional Kedurus- Karang Pilang Surabaya) - Sari, Febriana Fitria; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2020)
A woman in helping the family economy can be done through activities in the form of micro-activities such as trading. Many wives work as traders in the market Kedurus-Karang Pilang Surabaya to help improve the family economy. This research uses descriptive qualitative research, aims to determine the extent of the role of the wife in helping the family economy and what factors affect working wives. Data collected through observation, interviews, and documentation. The results of the research are the roles that they do as traders are not the main job, because they also get a living from their husbands. The wifes who works also does not forget the role of a housewife. In reviewing Islamic Economic the wife's work does not conflict with Islamic law and this is one form of devotion helping the husband to support their children. Factors that encourage wife’s to work are economy, level of education, and also self-actualization. Another factor found is to fill leisure time and hobbies